Factors Related to Complaints of Musculoskeletal Disorders (MSDS) in Cleaning Service Workers - Dalimunthe, Azila Rahimah; Tanjung, Nadya Ulfa; Astuty, Delfriana Ayu (Indonesian Journal of Global Health Research, 2024)
One of the jobs that has the potential to experience MSDs complaints is Cleaning Service workers who perform work repeatedly for a long time so that it can potentially damage the Musculoskeletal system. This study aims to determine the factors associated with MSDs complaints in Cleaning Service officers at RSUP Haji Adam Malik Medan. This study used quantitative analytical methods with Cross Sectional design, where the population amounted to 262 people. Determination of samples using the Lemeshow formula with stratified random sampling techniques with an error rate of 5%, obtained a sample of 150 people. Data results through statistical analysis using Chi square test. It is known that there is a relationship between age (pvalue = 0.039), gender (pvalue = 0.030), length of work (pvalue = 0.038), sports activities (0.028) with complaints of MSDs. With the existence of factors related to complaints of MSDs that are at risk of occurring in Cleaning Service workers of RSUP Haji Adam Malik Medan, it is expected for every worker to do adequate rest, by stretching if they start to feel sore in the joints or when do a job that can cause with complaints MSDs in order to still be able to do the job effectively.